SUBJECTIVE CHARACTER OF POLYTECHNIC EDUCATION - PROJECT EVALUATION - FRANC, Małgorzata (Trends in education, 2016)
This is a conceptual article and to some extent, methodical. It may constitute the beginning of research within the academic education of a phenomenological nature.In this study, it was assumed that: technical education consists of the education, as well as the technical training, while the technical upbringing is generally progress towards a skillful use of technology in the deliberately organized process impact per individual, or making permanent changes in its personality. Shaping the technical culture of a pupil is done by providing knowledge about the production techniques, experiencing technical situations, eliciting the respect for human creativity and technical products of this creation, skills training using the goods of modern technique. Technical training is geared to the realm of cognitive student, providing information and building a system of knowledge about the reality of the technical development of cognitive skills needed to receive, understand, interpret and verify technical phenomena.Subjectivity is a sense of being someone, having identity that distinguishes one individual from the other. Within its framework, a man believes that his own activity largely depends on himself alone. To become a subjective human being, it is needed to make educated assumptions about ourselves and choose our own path of development.With interest in the development of subjectivity in technical education carried out the project evaluation: "I have the time ...". The project participants were students of the Technical University of Lodz, the Education Technical Information.The advantage of the article is to show the signs of subjective education in the academic technical education in the perspective of students' opinions about education subject and orientation selection.
Keywords: Subjectivity; technical education; project evaluation